Non-neoplastic mortality of European workers who produce man made vitreous fibres. Issue 9 (1st September 1999) - Sali, D; Boffetta, P; Andersen, A; Cherrie, J W; Claude, J C; Hansen, J; Olsen, J H; Pesatori, A C; Plato, N; Teppo, L; Westerholm, P; Winter, P; et al.
Abstract : OBJECTIVE: To study mortality from non-neoplastic diseases among European workers who produce man made vitreous fibres (MMVF). METHODS: 11, 373 male workers were studied, who were employed for at least 1 year in the production of rock or slag wool (RSW), glass wool (GW), and continuous filament (CF) in 13 factories from seven European countries. Workers were followed up from the beginning of production, between 1933 and 1950 to 1990-2 and contributed 256, 352 person-years of observation. Standardised mortality ratios (SMRs) were calculated with national mortalities for reference; an internal exposure-response analyses based on multivariate Poisson regression models was also conducted. RESULTS: Mortality from bronchitis, emphysema, and asthma was not increased (SMR 1.03, 95% confidence interval (95% CI) 0.82 to 1.28). In RSW workers, there was no overall increase in mortality from non-malignant renal diseases (SMR 0.97, 95% CI 0.36 to 2.11), although there was the suggestion of an increase in risk with duration of employment. Mortality from ischaemic heart disease was not increased overall (SMR 1.03, 95% CI 0.96 to 1.11), but RSW and CF workers with > or = 30 years since first employment had a higher risk. RSW and CF workers showed an increased mortality from external causes, mainly motor vehicle accidents and suicide, which was higher among workers with a short duration of employment. CONCLUSIONS: Mortality from most non-neoplastic diseases does not seem to be related to employment in the MMVF industry. The results on mortality from ischaemic heart disease and non-malignant renal diseases, however, warrant further investigations.